Neogene-Quaternary evolution of the forearc and backarc regions between the Serre and Aspromonte Massifs, Calabria (southern Italy). (August 2018) - Tripodi, V.; Muto, F.; Brutto, F.; Perri, F.; Critelli, S.
Abstract: The role of tectonics in the Neogene-Quaternary evolution of the forearc basin, between the Serre and Aspromonte Massifs, located in the southern Calabria, is widely documented in the exposed sedimentary successions. The structuration of these different basins is due to the southeastward migration of the Calabrian Terranes, which led to the subduction of the Ionian lithosphere and the spreading of the Tyrrhenian back-arc basin. The area is dominantly displaced by two NW–SE and NE–SW oriented regional fault systems. These fault systems were active during the infilling of the Neogene-Quaternary basins, and represent complex tear fault systems that accommodated stress generated in the accretionary prism during the subduction of the Ionian lithosphere. Furthermore, these structures play a relevant role as part of recent seismotectonic processes, which controlled the Late Quaternary geodynamic evolution of the area.